COMPLEMENTARY BREASTFEEDING (MPASI) FEEDING PATTERNS AND HISTORY OF INFECTIOUS DISEASES IN STUNTED AND NON-STUNTED CHILDREN AGED 12-24 MONTHS IN THE GANTING COMMUNITY HEALTH CENTER AREA, GEDANGAN DISTRICT, SIDOARJO REGENCY - Nabila Aulia Rahmania; Amalia Ruhana (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Stunting is a condition of growth failure that occurs in toddlers due to chronic malnutrition that occurs in the First 1000 Days of Life (HPK), starting from the formation of the fetus until the child is 24 months old. Factors that influence the incidence of stunting are direct factors (food consumption, history of infectious diseases, breastfeeding practices, food availability) and indirect factors (economic conditions, health services, education level, social and cultural aspects). This study aims to determine the pattern of complementary feeding (MPASI) and history of infectious diseases, as well as differences in the pattern of complementary feeding (MP-ASI) and history of infectious diseases in stunted and non-stunted children in the work area of ​​Ganting Health Center, Gedangan District, Sidoarjo Regency. This study uses a quantitative approach with a 1:1 case control design paired by age and sex. The sample of this study was 60 children, consisting of 30 stunted children as the case group and 30 non-stunted children as the control group taken using a purposive sampling technique. Data collection on complementary feeding (MPASI) patterns was conducted using the Child Feeding Questionnaire (CFQ) and infectious disease history was obtained through interviews using a questionnaire. Data analysis used the McNemar test. The results of this study showed a significant difference in complementary feeding (MPASI) patterns (p = 0.035) and infectious disease history (p = 0.022) in stunted and non-stunted children in the working area of ​​the Ganting Health Center, Gedangan District, Sidoarjo Regency